Nonpivot and Implicit Projected Dynamical Systems on Hilbert Spaces - Monica Gabriela Cojocaru; Stephane Pia (Journal of Function Spaces and Applications)
This paper presents a generalization of the concept and uses of projected dynamical systems to the case of nonpivot Hilbert spaces. These are Hilbert spaces in which the topological dual space is not identified with the base space. The generalization consists of showing the existence of such systems and their relation to variational problems, such as variational inequalities. In the case of usual Hilbert spaces these systems have been extensively studied, and, as in previous works, this new generalization has been motivated by applications, as shown below.